(untitled) (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
The stress and displacement analysis is necessary to design and build efficiently any structure. In general, the current accepted procedures to design steel beams admit the linearelastic material behavior and are based on the assumptions adopted by the Euler-Bernoulli beam theory. However, it is critical to predict the behavior of the structural elements under plastic deformation, in order to understand the failure modes and the plastic hinges formation in steel beams. Accordingly, this paper proposes a theoretical procedure to evaluate stresses and displacements in steel beams under elastoplastic deformation, assuming the kinematic assumptions of the Euler-Bernoulli beam theory. Moreover, an iterative-incremental procedure based on the reformulated Prandtl-Reuss equations proposed by Mendelson is employed to compute the plastic strains, in the context of a secant or total elastoplastic formulation. In order to verify the proposed approach, its results are compared with those ones obtained by the finite element method analysis. This comparison demonstrates the effectiveness of the proposed model, and shows the possibility to realize more realistic and sophisticated analysis of steel beams using this approach.